Arthroscopic Acetabular Microfracture With the Use of Flexible Drills: A Technique Guide - Haughom, Bryan D. (Elsevier, 2014)
Chondral injuries of the hip joint are often symptomatic and affect patient activity level. Several procedures are available for addressing chondral injuries, including microfracture. Microfracture is a marrow-stimulating procedure, which creates subchondral perforation in the bone, allowing pluripotent mesenchymal stem cells to migrate from the marrow into the chondral defect and form fibrocartilaginous tissue. In the knee, microfracture has been shown to relieve pain symptoms. In the hip, microfracture has been studied to a lesser extent, but published studies have shown promising clinical outcomes. The depth, joint congruity, and geometry of the hip joint make microfracture technically challenging. The most common technique uses hip-specific microfracture awls, but the trajectory of impaction is not perpendicular to the subchondral plate. Consequently, the parallel direction of impaction creates poorly defined channels. We describe an arthroscopic microfracture technique for the hip using a flexible microfracture drill. The drill and angled guides simplify access to the chondral defect. The microfracture drill creates clear osseous channels, avoiding compaction of the surrounding bone and obstruction of the channels. Furthermore, this technique allows for better control of the angle and depth of the drill holes, which enhances reproducibility and may yield improved clinical outcomes.